Screening and Potential Testing of Metarhizium sp. Isolates for Controlling Lepidiota stigma (Fabricius) Larvae in Sugarcane (Saccharum officinarum L.) - Hanik Sulistyawati; Wiwin Windriyanti; Yenny Wuryandari (The University of Lampung, 2025)
Lepidiota stigma is a major pest contributing to the decline in sugarcane quality in East Java, necessitating effective control measures that support sustainable agriculture. Metarhizium anisopliae is an entomopathogenic fungus that acts as a natural enemy of L. stigma and is expected to control its infestations. This study aims to evaluate the potential of isolated strains in killing the larvae and to identify the compounds produced by Metarhizium spp. The research involved exploration, morphological identification, virulence testing, and compound analysis. Isolate screening was conducted in two stages: the first stage involved screening 20 isolates down to 5 potential ones, and the second stage assessed the characteristics and effectiveness of these 5 isolates in controlling L. stigma larvae at spore concentrations of 10⁶, 10⁷, and 10⁸ spores/ml in vitro. The parameters observed were larval mortality and metabolite content, analyzed using LC-HRMS (Liquid Chromatography High-Resolution Mass Spectrometry). Metarhizium spp. isolated from soil exploration showed an effect on L. stigma mortality. The fungus produced secondary metabolites, including destruxins A4, E, and Ed1, which contributed to the mortality of L. stigma larvae.